DESIGNING ESP COURSES IN INDONESIA: WHO IS RESPONSIBLE? - Askar, Kusni (English Department FBS UNP, 2009)
This article is intended to expose the implication of the results of two long surveys on the existence of ESP (English for Specific Purposes) as a compulsory subject with various names at different universities and colleges in Indonesia. In my first research, it was found out that ESP courses were misleading, misconduct, and amburadul. This situation happened not only at the small and developing universities but also at the established and well-known universities such as University of Indonesia, Padjadjaran University, and Gadjah Mada University. This year (2007), I conducted another research funded by the government on the same topic but different research subjects at some universities in West Sumatera (Andalas Univeristy, State University of Padang, Bung Hatta University, and Eka Sakti University), particularly atÂ three different study programs: Accounting, Engineering, and Physics.Â The data of this research were collected from totally 270 students, 12 ESP lecturers, 9 heads of study programs, 9 senior lecturers, and 3 TEFL experts. The findings of this research supported the previous findings that ESP faces critical problems in its design and implementation for limited professionalism of human resources. Almost all of the lecturers of the ESP courses were never been particularly prepared and trained to teach ESP. No other parties of stakeholders felt responsible for the ESP program, but the ESP lecturer. From the findings of the two researches, the question arises â€˜Who should be responsible for the ESP in Indonesia?â€ Â